Understanding the impact of the South African mineral resource royalty regime on tabular gold deposits: an approach for cut-off grade optimisation - Birch, Clinton (My University, 2022)
The South African mineral resource royalty introduced in 2010 employs a hybrid ad valorem approach in which the rate depends on the profitability ratio. This rate is then applied to the base of the total revenue from mineral sales. The fundamental purpose of this research is to understand how the profitability ratio in the mineral resource royalty interplays with the gold tax formula applied to South African gold mines and to develop an approach for cut-off grade optimisation. Narrow, tabular (Witwatersrand) gold mines are used for this study. The method developed is a mixed-integer (Excel Solver) cut-off grade optimiser that uses the mine’s block list and ore flow documents and feeds this into a financial cash flow which includes the appropriate royalty and income tax formula. This could then be utilised to test various mineral resource royalty cost options. This research shows that the impact of the royalty is minimal because the analysis convincingly proves that it is more neutral than expected. Simply ignoring the mineral resource royalty costs when determining the cut-off grade by a break-even approach increases the profit slightly compared to including the expected costs. However, resource utilisation increases significantly, allowing the benefits of reduced development costs. Furthermore, life is added to the mines, which is very beneficial in a country with high unemployment. Total revenue and tax contributions also increase significantly. Further gains can be achieved using the optimiser model developed for this study that recognises the profitability aspect of the mineral resource royalty and the income tax (gold tax) formulae. This optimiser also allows a multiplecriteria cut-off grade optimising approach and grade estimation uncertainties to be considered. This is an appropriate method to optimise the capability of the ore body and should be considered by the industry when deciding and reporting mineral reserve statements for narrow-reef gold mining.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Engineering to the Faculty of Engineering and the Built Environment, School of Mining Engineering, University of the Witwatersrand, Johannesburg, 2022